PENGGUNAAN MODEL TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN KREATIVITAS PENGEMBANGAN TARI PADA SISWA KELAS X SMA - Herdianti, Erni; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is low student creativityÂ in dance. This is due to a lack of stimulus to motivate students to do a dance. The purpose of this research is to describe the learning process and increasing student creativity in dance used the Teams Games Tournament learning model. The method used in this research is descriptive method and qualitative approach. The form of research is classroom action research. Research subjects are grade X MIA 2 students of Senior High School 9 Pontianak. Data collection technique in this research is closed observation directly, interview technique, documentation and skill test technique. In this research used triangulation technique to test the validity of data. The researcher used 3 steps to analyze the data, that is : reduction, display data, and verification.The results of this research are shows an increase in dace creativity to students from learning process that has been carried out. The process carried out on students grade X MIA 2 of Senior High School 9 Pontianak used Teams Games Tournament learning model. The researcher gave a competition consisting of 3 games with they teams. The games are to develop malay dance basic. There are 3 steps of research, that is Pre Cycle, Cycle 1 and Cycle 2. After learning process from cycle 1 to cycle 2 and step student creativity in develop malay danceÂ basic increase with an average value of 68 on cycle 1 still in the â€œUnskilledâ€ category to average value 76 on cycle 2Â â€œSkilledâ€ category.Keywords : Learning Model, Teams Games Tournament, Dance Creativity.